CURRENT MARKET TRENDS IN MARKETING AUTOMATION SYSTEMS - С. О. Солнцев; В. К. Биба (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2025)
The purpose of the study is a comprehensive analysis of the main products of the leaders of the global market of marketing automation systems, which will allow us to identify the most promising of them from the point of view of practical implementation. Research methodology. To achieve the goal of the study, a comprehensive approach, general scientific and special research methods were used. Results. It is proven that today the general trend in market development is the broad and comprehensive integration of AI and machine learning into most functions of marketing automation systems. The practical significance of the research results is that the identified key trends in the development of the marketing automation systems market will help the company to better navigate and choose the most promising products of the leaders of the specified market.